Cost-Effectiveness of Nivolumab Plus Cabozantinib Versus Sunitinib as a First-Line Treatment for Advanced Renal Cell Carcinoma in the United States - Li, SiNi; Li, JianHe; Peng, LiuBao; Li, YaMin; Wan, XiaoMin (Frontiers in Pharmacology, 2021)
Background: In a recent randomized, phase 3 trial (CheckMate 9ER), nivolumab combined with cabozantinib significantly improved patient outcomes compared with sunitinib. However, the cost effectiveness of these novel agents for untreated advanced renal cell carcinoma (aRCC) remains unknown. Materials and Methods: We constructed a microsimulation decision-analytic model to measure the healthcare costs and outcomes for nivolumab plus cabozantinib compared with sunitinib for patients with aRCC. The transition probability of patients was calculated from CheckMate 9ER by using parametric survival modelling. Lifetime direct medical costs, life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were estimated for nivolumab-plus-cabozantinib treatment compared with sunitinib from a US payer perspective. We conducted one-way and probabilistic sensitivity analyses and a series of scenario analyses to evaluate model uncertainty. Results: Nivolumab plus cabozantinib was associated with an improvement of 0.59 LYs and 0.56 QALYs compared with sunitinib. However, incorporating nivolumab plus cabozantinib into first-line treatment was associated with significantly higher lifetime costs ($483,352.70 vs $198,320.10), causing the ICER for nivolumab plus cabozantinib to be $508,987/QALY. The patients’ age of treatment, first-line utility and cost of nivolumab had the greatest influence in the model. The outcomes were robust when tested in sensitivity and scenario analyses. Conclusions: For aRCC, substituting nivolumab plus cabozantinib in the first-line setting is unlikelihood to be cost effective under the current willingness-to-pay threshold ($150,000/QALY). Significant price decreases for nivolumab used in first-line therapy would be needed to drop ICERs to a more diffusely acceptable value.